Temporal trends in mercury, methylated mercury and their relation to dissolved organic carbon - Galloway, Jason (2015)
Mercury (Hg) and methylated mercury (MeHg) are major environmental pollutants in boreal regions. Dissolved organic carbon (DOC) has been established by a number of studies to be a key vector in the mobilisation of terrestrial Hg and MeHg to aquatic environments where Hg and MeHg can then enter the food chain. This study examined long-term trends in DOC (1986-2012), Hg (1993-2000) and MeHg (1993-2000) stream water concentrations in three sites (C2- forest, C4- mire and C7 - mixed) in the Svartberget catchment in northern Sweden. A positive trend was found in DOC concentrations over the last decade while results for Hg and MeHg were inconclusive. The Riparian Flow-Concentration Integration Model (RIM) in three forms (RIMstatic, RIMdyn and RIMmed) was then used to simulate stream water concentrations using flow as an input and model residuals were examined to provide insight into solute dynamics in the three study sites through time. Model residuals were compared and the Nash-Sutcliffe model efficiency coefficient was used to assess the performance of each model at each site.